Inside Cover: Encapsulation of Cyclotetramethylenetetranitramine (HMX) by Electrostatically Self‐Assembled Graphene Oxide for Desensitization (Prop., Explos., Pyrotech. 9/2017). Issue 9 (8th September 2017) - Liu, Tao; Geng, Chengzhen; Zheng, Baohui; Li, Shangbin; Luo, Guan
Abstract : The inside cover picture shows the overall preparation of HMX@GO composite and the SEM images of HMX and HMX@GO composites. The preparation involves two steps: 1) HMX surface was modified by APS to obtain APS‐modified HMX particles (s‐HMX). 2) By adopting appropriate pH values, the surfaces of s‐HMX particles and GO were supposed to be oppositely charged. So HMX@GO composite could be fabricated via the electrostatic interaction between positively charged s‐HMX and negatively charged GO in aqueous suspension. The SEM images shows that the surface of HMX particles is smooth with some groove defects on micron scale, and the distribution of the defects is uniform. However, after the assembly between s‐HMX and GO, the surface of HMX@GO composite particles is well coated with a compact wrinkled layer. More details can be found in the Full Paper by Dr. Chengzhen Geng et al. onpage 1057 .